2011
DOI: 10.1016/j.jacc.2011.04.017
|View full text |Cite
|
Sign up to set email alerts
|

High On-Treatment Platelet Reactivity After Prasugrel Loading Dose and Cardiovascular Events After Percutaneous Coronary Intervention in Acute Coronary Syndromes

Abstract: Despite the use of prasugrel, a significant number of patients undergoing PCI in the setting of acute coronary syndromes do not achieve optimal PR inhibition. Such patients have a higher risk for MACE after PCI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
103
1
7

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 196 publications
(121 citation statements)
references
References 17 publications
10
103
1
7
Order By: Relevance
“…Similarly, we expected that additional administration of 30 mg of prasugrel in HTPR patients who had received a 600 mg loading dose of clopidogrel would decrease PRI to a value comparable with that observed in clopidogrel-naive patients after treatment with a 60 mg loading dose of prasugrel (34.3 ± 23.1%) [19]. Additionally, we anticipated in our prasugrel-treated patients to obtain PRI values at 30 days comparable to these observed in the TRITON-TIMI 38 platelet substudy at this time point (33.6 ± 2.9%) [20].…”
Section: Statistical Analysis and Sample Size Calculationmentioning
confidence: 74%
See 1 more Smart Citation
“…Similarly, we expected that additional administration of 30 mg of prasugrel in HTPR patients who had received a 600 mg loading dose of clopidogrel would decrease PRI to a value comparable with that observed in clopidogrel-naive patients after treatment with a 60 mg loading dose of prasugrel (34.3 ± 23.1%) [19]. Additionally, we anticipated in our prasugrel-treated patients to obtain PRI values at 30 days comparable to these observed in the TRITON-TIMI 38 platelet substudy at this time point (33.6 ± 2.9%) [20].…”
Section: Statistical Analysis and Sample Size Calculationmentioning
confidence: 74%
“…However, recent studies indicated that the phenomenon of HTPR also refers to subjects treated with prasugrel [20,21]. The prevalence of HTPR defined as the PRI value ≥ 50% measured 6-12 h after the administration of a 60 mg loading dose of prasugrel among 301 ACS patients successfully treated with PCI in a multicenter French study was 25.2% [19]. This rate corresponds with the prevalence of HTPR on prasugrel at 30 days in the TRITON-TIMI 38 platelet substudy (24% among 51 patients) [20], based on the same definition as applied by Bonello et al [19].…”
Section: Discussionmentioning
confidence: 99%
“…According to an earlier trial, more than half of the STEMI patients treated with LD of integral ticagrelor still have HRPR up to 4 hours after administration of the drug. (7) Given the fact that suboptimal platelet inhibition is an important predictor of ischemic complications, such as stent thrombosis, (19) there is a time window after primary PCI, in which patients are at increased risk for ischemic complications.…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, Valgimgli et al17 reported that treatment with tirofiban, in patients who had HPR with clopidogrel, resulted in a 40% reduction in the incidence of PMI compared with clopidogrel. Although it has been assumed that the use of potent P2Y 12 inhibitors would overcome the problem of HPR, recent data4 showed that HPR was still observed in a significant number of patients (25.2%) with prasugrel, a potent P2Y 12 inhibitor.…”
Section: Discussionmentioning
confidence: 99%